Social dimensions in global ethics. New perspectives in education - Fracapani Cuenca de Cuitiño, Marta T. (Acta Bioethica, 2013)
This paper refers to some landmarks to consider in university training programs, with the aim to adopt a wide point of view by reflecting on experience, knowledge and learning, including the search for comprehending the relations of our lives and of people around the world. Furthermore, it refers to local experience in the province of Mendoza, Argentina. The elaboration of a norm to rule professionals in residence is promoted based on their evaluation, favoring deep changes, such as actions between sectors, organization and net membership and the first level priority on health and inter discipline. The residences of health care professionals, as educational resource to train citizens and critical professionals prepared for a globalized world, is part of the transforming process in health care, which could help to give priority to this value in all policies. Bioethics, as applied ethics, provides its method and lays the foundation for justice in the system.